Dynamics of Aerenchyma Distribution in the Cortex of Sulfate-deprived Adventitious Roots of Maize - BOURANIS, DIMITRIS L. (Oxford University Press, 2006)
• Background and Aims Aerenchyma formation in maize adventitious roots is induced in nutrient solution by the deprivation of sulfate (S) under well-oxygenated conditions. The aim of this research was to examine the extent of aerenchyma formation in the cortex of sulfate-deprived adventitious roots along the root axis, in correlation with the presence of reactive oxygen species (ROS), calcium levels and pH of cortex cells and root lignification. • Methods The morphometry of the second whorl of adventitious (W2) roots, subject to S-deprivation conditions throughout development, was recorded in terms of root length and lateral root length and distribution. W2 roots divided into sectors according to the mean length of lateral roots, and cross-sections of each were examined for aerenchyma. In-situ detection of alterations in ROS presence, calcium levels and pH were performed by means of fluorescence microscopy using H(2)DCF-DA, fluo-3AM and BCECF, respectively. Lignification was detected using the Wiesner test. • Key Results S-deprivation reduced shoot growth and enhanced root proliferation. Aerenchyma was found in the cortex of 77 % of the root length, particularly in the region of emerging or developing lateral roots. The basal and apical sectors had no aerenchyma and no aerenchyma connection was found with the shoot. S-deprivation resulted in alterations of ROS, calcium levels and pH in aerenchymatous sectors compared with the basal non-aerenchymatous region. Lignified epidermal layers were located at the basal and the proximal sectors. S-deprivation resulted in shorter lateral roots in the upper sectors and in a limited extension of the lignified layers towards the next lateral root carrying sector. • Conclusions Lateral root proliferation is accompanied by spatially localized induced cell death in the cortex of developing young maize adventitious roots during S-deprivation.